DEMOCRATIZATION IN EGYPT AND INDONESIA (COMPARATIVE STUDY IN ENDING AUTHORITARIAN REGIME) - Bastian Harwidiansyah (Universitas Muhammadiyah Yogyakarta, 2013)
DEMOCRATIZATION IN EGYPT AND INDONESIA (COMPARATIVE STUDY IN ENDING AUTHORITARIAN REGIME)